Representation Learning Using Multi-Task Deep Neural Networks for Semantic Classification and Information Retrieval - Liu, Xiaodong; Gao, Jianfeng; He, Xiaodong; Deng, Li; Duh, Kevin; Wang, Ye-Yi (NAACL, 2015)
Methods of deep neural networks (DNNs) have recently demonstrated superior performance on a number of natural language processing tasks. However, in most previous work, the models are learned based on either unsupervised objectives, which does not directly optimize the desired task, or singletask supervised objectives, which often suffer from insufficient training data. We develop a multi-task DNN for learning representations across multiple tasks, not only leveraging large amounts of cross-task data, but also benefiting from a regularization effect that leads to more general representations to help tasks in new domains. Our multi-task DNN approach combines tasks of multiple-domain classification (for query classification) and information retrieval (ranking for web search), and demonstrates significant gains over strong baselines in a comprehensive set of domain adaptation.